Imaging peripheral lymphatic dysfunction in chronic conditions - Sevick-Muraca, Eva M.; Fife, Caroline E.; Rasmussen, John C. (Frontiers in Physiology, 2023)
The lymphatics play important roles in chronic diseases/conditions that comprise the bulk of health care worldwide. Yet the ability to routinely image and diagnose lymphatic dysfunction, using commonly available clinical imaging modalities, has been lacking and as a result, the development of effective treatment strategies suffers. Nearly two decades ago, investigational near-infrared fluorescence lymphatic imaging and ICG lymphography were developed as routine diagnostic for clinically evaluating, quantifying, and treating lymphatic dysfunction in cancer-related and primary lymphedema, peripheral vascular disease, and more recently, autoimmune and neurodegenerative disorders. In this review, we provide an overview of what these non-invasive technologies have taught us about lymphatic (dys)function and anatomy in human studies and in corollary animal studies of human disease. We summarize by commenting on new impactful clinical frontiers in lymphatic science that remain to be facilitated by imaging.